Psoriatic arthritis is associated with myocardial repolarization dysregulation as assessed by the QTc interval and the Tp-e/QTc ratio - Erken Pamukcu, Hilal; Pamukcu, Melih (Journal of Surgery and Medicine, 2020)
Aim: An increased risk of arrhythmia has been shown in patients with psoriatic arthritis (PsA). Tp-e interval and Tp-e/QT ratio are considered useful markers for the assessment of myocardial repolarization heterogeneity. In present study we aim to investigate the characteristics of ventricular repolarization on the basis of QTc interval and Tp-e/QTc ratio in patients PsA. Methods: This cross-sectional observational study included patients with psoriatic arthritis who were over 18 years of age. A control group was created with healthy volunteers. The diagnosis of psoriatic arthritis were done according to the CASPAR criteria. QT interval, corrected QT (QTc), Tp-e interval, Tp-e/QT ratio and Tp-e/QTc ratio were measured from the 12-lead electrocardiograms(ECG) of the PsA patients and control group. Results: The study population consisted of 82 patients with PsA and 82 healthy volunteers. According to electrocardiographic parameters the heart rate was similar in both groups, but QT, QTc, Tp-e intervals; Tp-e /QT and Tp-e/ QTc ratios were significantly higher in the PsA group. The median Tp-e/QTc ratio of the patients with PsA was significantly higher than the median Tp-e/QTc ratio of the control group (0.21 (0.20-0.25) vs. 0.18 (0.17-0.19, P<0.001). The correlation analysis showed a weak correlation between Tp-e/QTc ratio and CRP value (r=0.197, P=0.012). Conclusions: This is the first study to demonstrate the prolongation of the Tp-e/QTc ratio in patients with PsA. Prospective clinical studies to observe clinical importance of this finding particularly with regard to the arrhythmias and sudden death may be more valuable.